Complications in the first 10 phacoemulsification cataract surgeries with and without prior simulator training - Lucas, Larisa [UNESP]; Schellini, Silvana Artioli [UNESP]; Lottelli, Antonio Carlos [UNESP] (Consel Brasil Oftalmologia, 2019)
Purpose: To evaluate whether training medical residents with the Eyesi (R) cataract surgery simulator reduces the occurrence of intraoperative complications. Methods: This was a retrospective study in which the first 10 phacoemulsification surgeries performed by two groups of second-year ophthalmology residents were evaluated, during 2014 and 2015. The first Group consisted of seven residents from 2014 who had not had previous training with the simulator. The second Group was formed of seven residents in 2015, who had completed the C-level (intermediate) training with the simulator before beginning surgery on patients. We then compared these two groups regarding the frequency of occurrence of the four main intraoperative surgical complications: posterior capsule rupture, aphakia, and nucleus fragment dislocation into the vitreous, and extracapsular conversion. Results: A total of 140 surgeries were performed, 70 by Group 1 and 70 by Group 2. The total number of complications was 19 (27.14%) in Group 1 and nine (12.86%) in Group 2, and this reduction was significant (p=0.031). Fourteen (20%) surgeries in Group 1 and seven (10%) in Group 2 had complications. The complications were 13 posterior capsule rupturvs (18.57%) in Group 1 and seven (10%) in Group 2; three eyes had nucleus fragment dislocations (4.29%) in Group 1, but only one (1.43%) in Group 2; two extracapsular conversions 2.86%) occurred in Group 1 and one (1.43%) in Group 2; and there was one aphakia (1.43%) in Group 1. Conclusions: The training with the Eyesi (R) cataract surgery simulator significantly reduced the total number of intraoperative complications in the first 10 phacoemulsification cataract surgeries performed by ophthalmology residents.
Keywords: Simulation; Computer simulation; Phacoemulsification/adverse effects; Residents/education; Medical staff, hospital; Teaching